A strategy of finely optimizing WOX electrochromic layers for application in flexible ATF-ECDs. (20th January 2022) - Wang, Rui; Lin, Han; Zhu, Hongbing; Wan, Meixiu; Shen, Kai; Mai, Yaohua
Abstract: In this study, tungsten oxide (WOX ) thin films were prepared by reactive magnetron sputtering at different oxygen (O2 ) fluxes for application in flexible all-thin-film electrochromic devices (ATF-ECDs) with a device configuration of PET/ITO/NiOX /Ta2 O5 /WOX /ITO. The target voltage vs. O2 flux curve presents two sputtering mode zones, where distinct target voltages reflect the specific target surface states. The WOX thin film deposited at the O2 flux of 4.5 sccm, which sites at the onset point reaching to the maximal target voltage, exhibits amorphous structure, relatively loose morphology, proper chemical compositions, high light transmittance and best electrochemical properties. The corresponding flexible ATF-ECD performs excellent electrochromic performances with high light modulation of up to 70%, fast response time and the highest coloration efficiencies at both bleaching and coloring steps.